2013
DOI: 10.1080/10810730.2013.778364
|View full text |Cite
|
Sign up to set email alerts
|

The Intersection of Gender and Place in Online Health Activities

Abstract: This study examines how rurality and gender are related to online health activities. Rural women face greater health risks and yet have access to a weaker health system infrastructure, which has resulted in a health disadvantage. New health information technologies may ameliorate some of these disparities; thus, the authors examine the relevance of gender and place in going online to search for health information, buy medicines, participate in health-related support groups, communicate with physicians, or main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 41 publications
1
2
0
Order By: Relevance
“…This result is consistent with the literature reporting a steady increase over the years of older adults who are OHIS (15). In addition, we found that across each wave, young-old older adults were more likely to be OHIS, which is also consistent with the literature (4,(16)(17)(18). Researchers also need to be cognizant of rapid changes, like COVID-19, that create new opportunities and new challenges for older adults to search for health resources via the Internet.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This result is consistent with the literature reporting a steady increase over the years of older adults who are OHIS (15). In addition, we found that across each wave, young-old older adults were more likely to be OHIS, which is also consistent with the literature (4,(16)(17)(18). Researchers also need to be cognizant of rapid changes, like COVID-19, that create new opportunities and new challenges for older adults to search for health resources via the Internet.…”
Section: Discussionsupporting
confidence: 91%
“…In addition to age, gender, education, annual income, and health status influence older adults' level of engagement with OHIS. Older adults who are female and who have more chronic health symptoms are more likely to be OHIS (16)(17)(18)(19)(20), whereas older adults with less than a high school education and an annual household income of <$25,000 are less likely to be OHIS (4).…”
Section: Introductionmentioning
confidence: 99%
“…We conducted a sensitivity analysis to test the Bass model’s parameters and create a possible range of future PHR uptake by varying the technology introduction year [ 22 ]. The oldest estimates for PHRs entering the market place with the minimum functionalities described above puts their introduction around the year 2001 [ 23 ].…”
Section: Methodsmentioning
confidence: 99%